Effect of phacoemulsification on intraocular pressure in patients with primary open angle glaucoma and pseudoexfoliation glaucoma - Jesus Jimenez-Roman; Gabriel Lazcano-Gomez; Karina Martínez-Baez; Mauricio Turati; Rosario Gulías-Cañizo; Luis F. Hernández-Zimbrón; Lenin Ochoa-De la Paz; Rubén Zamora; Roberto Gonzalez-Salinas (International Journal of Ophthalmology, 2017)
AIM: To compare the effect of phacoemulsification on intraocular pressure (IOP) in patients with primary open angle glaucoma (POAG) and pseudoexfoliation glaucoma (PXG). METHODS: A retrospective comparative case series conducted at the Glaucoma Department at the Association to Prevent Blindness in Mexico. The study enrolled consecutive patients having phacoemulsification with intraocular lens (IOL) implantation and a diagnosis of POAG or PXG. Data about IOP values and number of glaucoma medications used was collected at baseline, 1, 3, 6 and 12mo postoperatively. RESULTS: The study enrolled 88 patients (88 eyes). After phacoemulsification, there was a statistically significant reduction in IOP values and glaucoma medications use compared to baseline in both POAG and PXG patients (P<0.001). In the POAG group, a 20% decrease in IOP values was evidenced, and a 56.5% reduction in the number of medications used at the one-year follow-up. The PXG group showed a 20.39%, and a 34.46% decrease in IOP and number of medications used, respectively. A significant difference in the mean ΔIOP (postoperative changes in IOP) was evidenced between groups (P=0.005). The reduction of the postsurgical IOP mean values in both groups, the POAG group showed a greater reduction in IOP values compared to the PXG group. CONCLUSION: In both types of glaucoma, phacoemulsification cataract surgery can result in a significant IOP reduction (20%) over a 12mo follow-up period. The number of medications used is also significantly reduced up to 12mo after surgery, especially in the PXG group.